Hubungan Pola Perdarahan Uterus dengan Kadar Estradiol pada Akseptor Kontrasepsi Injeksi DMPA - Enny S Pamuji, Djaswadi Dasuki, M. Hakimi (Berita Kedokteran Masyarakat (BKM), 2008)
Background: Bleeding disturbances are the main complaint that cause most DMPA users discontinuing contraceptive use. Mechanism underlying the bleeding disturbances is not clear. It is presumed that the condition is related to fluctuation of estradiol level or to low persistent estradiol level Objective: 1. To evaluate an association between bleeding pattern and estradiol level of DMPA users after 3, 6, 9, 12 months use. 2. To evaluate an association between estradiol level and length of use. 3. To evaluate an association between bleeding pattern and estradiol level, body mass index (BMI), age, parity, total cholesterol level of DMPA users.Design: Observational study, secondary analysis nested on “Randomized Controlled Trial Planibu® and Depo Progestin®”Material and Method:  Seventy DMPA users received injection every 3 months for 12 months. Before injection was administered, venous blood was taken and examination of estradiol level was done using Enzyme Imuno Absorbent Assay (ELISA). In addition, in-depth interview was also done on bleeding pattern for the last reference period (90 days). Subject was classified according to their bleeding pattern into groups of amenorrhea, oligomenorrhea, spotting, and bleeding,Results: All research subjects indicated low estradiol concentration with an average concentration less than 150 pg/ml. There was a correlation between length of usage and estradiol level; estradiol level after 12 months of usage was less than 100 pg/ml. There was no different between bleeding pattern and estradiol in month 3, 6, 9,12  using bivariate analysis with t-test with amenorrhea group as reference and p > 0,05. T-test and Chi Square analyses using amenorrhea group as reference stated that there was no association between bleeding pattern and age, BMI, and parity. Using multivariate analysis with Multinomial Logistic Regression, it was stated that correlation between estradiol concentration and bleeding  pattern was not affected by age, body mass index, or total cholesterol level. There was an association between bleeding pattern and cholesterol level using bivariate and multivariate analyses.Conclusion:  1. Estradiol level in various bleeding pattern after 3,6,9,12 month of usage was not different. 2. There was correlation between low estradiol level and length of usage. 3. Association between bleeding pattern and estradiol level was not influenced by age, parity and body mass index, and total cholesterol level.Keywords: bleeding pattern, estradiol, DMPA, injectable contraception